A Developmental Eye Tracking Investigation of Cued Task Switching Performance. Issue 4 (8th January 2021) - Zheng, Annie; Church, Jessica A.
Abstract : Children perform worse than adults on tests of cognitive flexibility, which is a component of executive function. To assess what aspects of a cognitive flexibility task (cued switching) children have difficulty with, investigators tested where eye gaze diverged over age. Eye‐tracking was used as a proxy for attention during the preparatory period of each trial in 48 children ages 8–16 years and 51 adults ages 18–27 years. Children fixated more often and longer on the cued rule, and made more saccades between rule and response options. Behavioral performance correlated with gaze location and saccades. Mid‐adolescents were similar to adults, supporting the slow maturation of cognitive flexibility. Lower preparatory control and associated lower cognitive flexibility task performance in development may particularly relate to rule processing.